Feasibility and Safety of Perioperative Chemotherapy With Fluorouracil Plus Leucovorin, Oxaliplatin, and Docetaxel for Locally Advanced Gastric Cancer Patients in China - Sah, Birendra Kumar; Xu, Wei; Zhang, Benyan; Zhang, Huan; Yuan, Fei; Li, Jian; Liu, Wentao; Yan, Chao; Li, Chen; Yan, Min; Zhu, Zhenggang (Frontiers in Oncology, 2021)
Background: Neoadjuvant fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) has shown significant benefits for gastric cancer patients. However, it has not been well accepted in Asian countries. We conducted a prospective study on the safety and feasibility of the FLOT regimen in Chinese patients. Methods: Patients with adenocarcinoma of the stomach or esophagogastric junction received 4 cycles of neoadjuvant chemotherapy (NAC) and 4 cycles of adjuvant chemotherapy (AC) with the FLOT regimen. The completion status of chemotherapy, adverse events, postoperative morbidities, and pathological tumor regression were analyzed. The two-year overall survival (OS) and relapse-free survival are presented. Results: Altogether, 10 patients were enrolled, and all patients completed 4 cycles of neoadjuvant chemotherapy. There were no severe hematological adverse events (grade 3 or above), except for a case of grade 3 anemia. All 10 patients underwent radical gastrectomy. Nine patients had R0 resection, and 3 patients had complete or subtotal pathological tumor regression. Nine patients completed 4 cycles of adjuvant chemotherapy, but only one patient completed the full dose of adjuvant chemotherapy. The dose of adjuvant chemotherapy was reduced by 25% or less in the other patients. The median follow-up time was 23.13 months, 8 patients achieved the overall survival endpoint, and 7 patients had relapse-free survival for this period. Two patients died of disease progression. Conclusions: Our study demonstrates that the neoadjuvant FLOT regimen is safe and effective for Chinese patients. Dose adjustment is necessary for adjuvant chemotherapy. The pathological regression and survival rates need reevaluation in a larger cohort.